Procedure in the prevention and nurturing of inflammatory changes of oral mucositis among patients treated for oncological conditions - Kamińska, Marzena; Juszkiewicz, Magdalena; Tymicka, Renata; Bronikowska, Agnieszka; Kolak, Agnieszka (Medical Studies/Studia Medyczne, 2016)
Oral mucositis is a serious complication occurring in the process of chemotherapy and/or radiotherapy. Ailments related to oral mucositis may bring about pain, reduce the amount of food intake, and eventually deteriorate the quality of life. This complication arises after radiotherapy, chemotherapy, transplantation of haematopoietic stem cells, and after molecularly targeted therapy. These symptoms may be the result of delay of treatment or dose reduction of successive cycles of chemotherapy, which, consequently, may have an impact on oncological treatment.